Exploring Secondary Biotinidase Deficiency and Biotin Supplementation in PMM2-CDG - Himmelreich, Nastassja; Garbade, Sven F.; Okun, Jürgen G.; Hengst, Simone; Geiger, Virginia; Barone, Rita; Wortmann, Saskia B.; Thiel, Christian (Neuropediatrics, 2025)
The congenital disorders of glycosylation (CDG) encompass >190 multiorgan disorders with predominantly neurodevelopmental phenotypes with no causative treatment available. The glycoprotein biotinidase (BTD) provides biotin, an essential cofactor for carboxylases in ubiquitous metabolic pathways. Individuals with (partial) BTD deficiency (BTDD) and CDG patients show overlapping phenotypes like movement disorders, seizures, and neurodevelopmental issues. Biotin is a water-soluble, inexpensive, and safe food supplement. Patients with primary BTDD respond well to oral biotin supplement. We here explore secondary BTDD and the effect of biotin supplementation in PMM2-CDG in an initial open-label study.BTD activity in dried blood spots from 29 individuals with PMM2-CDG indicated a mean reduction to 27% (range: 23.0–40.5%) at group level. Patients (mean: 19.6 ± 11.9 years) were supplemented with 10 mg biotin daily for 12 months. The parents/caretaker reported positive responses in 62 to 69% of patients across seven (performance, social, at home, self-control, self-care, leisure, health) of the nine categories covered by the Adaptive Behavior Assessment System-II (ABAS-II) questionnaires. The reported positive effect of biotin supplementation differed between age groups, ranging from 54% (16–43 years) via 62% (2–5 years) to 80% (6–13 years). Its effect was reported to be the highest in the moderate to severely affected patient subgroups, with significant improvements in home functioning, health, performance, leisure, self-control. No adverse effects were reported.Given the absence of other treatments, the supportive effect of Biotin in PMM2-CDG deserves further exploration.
Keywords: congenital disorders of glycosylation; therapy; vitamin H; biotinidase deficiency; treatment; seizures; movement disorder; rare disease